2016
DOI: 10.1016/j.amjcard.2016.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Statin Use and Mortality in Community-Dwelling Frail Older Patients With Coronary Artery Disease

Abstract: Clinical decision-making for statin treatment in older patients with coronary artery disease (CAD) is under debate, particularly in community-dwelling frail patients at high risk of death. In this retrospective observational study on 2,597 community-dwelling patients aged ≥65 years with a previous hospitalization for CAD, we estimated mortality risk assessed with the Multidimensional Prognostic Index (MPI), based on the Standardized Multidimensional Assessment Schedule for Adults and Aged Persons (SVaMA), used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 26 publications
2
31
0
3
Order By: Relevance
“…Very recently, the MPI-SVaMA has been implemented in older people to evaluate whether a different individual prognostic profile was associated with different mortality rates after treatment for specific disorders (ie, statins in older patients with diabetes mellitus 41 or coronary artery disease 42 as well as anticoagulants in older patients with atrial fibrillation). 43 These studies suggested that full access to prognostic information derived from CGA-based predictive tools better equips physicians to make clinical decisions aligned with their patients’ needs in terms of safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, the MPI-SVaMA has been implemented in older people to evaluate whether a different individual prognostic profile was associated with different mortality rates after treatment for specific disorders (ie, statins in older patients with diabetes mellitus 41 or coronary artery disease 42 as well as anticoagulants in older patients with atrial fibrillation). 43 These studies suggested that full access to prognostic information derived from CGA-based predictive tools better equips physicians to make clinical decisions aligned with their patients’ needs in terms of safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of older ambulatory populations have reported underuse of secondary prevention medications after AMI . Likewise, studies of NH populations have reported underuse of individual secondary prevention medication classes .…”
Section: Discussionmentioning
confidence: 99%
“…RCTs that have demonstrated that the use of beta‐blocker, statin, and antiplatelet therapy after AMI substantially reduces mortality in individuals younger than 75 support guideline recommendations . Observational studies have extended some of these findings to community‐dwelling people beyond age 85 years . Even frail older NH residents may benefit …”
mentioning
confidence: 93%
“…On the one hand, frailty is associated with increased cardiovascular risk; on the other hand, frail and comorbid patients are more susceptible to adverse drug reactions and pharmacological interactions. In general, though, frail individuals are less likely to be treated …”
Section: Clues To Optimal Treatment Choicementioning
confidence: 99%